Investigating the transcriptional regulation of small RNA expression in Salmonella enterica serovar Typhimurium - Colgan, Aoife (Trinity College (Dublin, Ireland). Department of Microbiology, 2015)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is an important foodborne pathogen that causes self-limiting gastroenteritis, or more serious systemic infections in susceptible hosts. S. Typhimurium can infect a wide host range and encounters a series of stressful conditions within various host environments. S. Typhimurium expresses a Type Three Secretion System (TTSS) encoded on a pathogenicity island (SPI1), to mediate invasion of the host intestinal epithelium. Once internalised, S. Typhimurium survives and replicates within the Salmonella containing vacuole (SCV). S. Typhimurium expresses a second TTSS, encoded on a second pathogenicity island (SPI2), to survive the harsh intracellular environment and establish systemic infection.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin